Smoking and quit attempts during pregnancy and postpartum: a longitudinal UK cohort - Cooper, Sue; Orton, Sophie; Leonardi-Bee, Jo; Brotherton, Emma; Vanderbloemen, Laura; Bowker, Katharine; Naughton, Felix; Ussher, Michael; Pickett, Kate E.; Sutton, Stephen; Coleman, Tim (BMJ Publishing Group Ltd, 2017)
Objectives Pregnancy motivates women to try stopping smoking, but little is known about timing of their quit attempts and how quitting intentions change during pregnancy and postpartum. Using longitudinal data, this study aimed to document women’s smoking and quitting behaviour throughout pregnancy and after delivery.